None a stranger there: England and/in Europe on the early modern stage - Oldenburg, Scott; Pangallo, Matteo (Strode studies in early modern literature and culture, 2025)
"None a Stranger There offers a collection of wide-ranging essays that explore the creation and understanding of English identity through the lens of early modern drama. Drawing together a rich array of disciplines-literary criticism, theater history, linguistics, book history, and performance studies-the scholars in this collection illuminate how diverse or competing notions of "Englishness" can be seen and studied in early modern English plays. They are an especially fertile site of study because they enabled collective performances in a variety of settings, such as public theaters, royal courts, and streets. They engaged with live audiences from a cross section of society. The contributors also draw parallels in plays of the period between past and present. They identify vivid struggles over controversies-especially Brexit and neonationalism-that still bedevil Britain and much of the western world: attitudes about and experiences of immigrants; xenophobia and tolerance; multiculturalism, assimilation, and hybridity; patriotism and jingoism; racial and ethnic identity; border-making and border-crossing; transnational itinerancy; and other topics. None a Stranger There provides a nuanced understanding of how early modern dramatists shaped and responded to questions about English identity and its relationship with Europe and beyond. It emphasizes the fluidity and complexities of national identity, reminding us that these debates remain deeply relevant in an interconnected world. CONTRIBUTORS Heather Bailey / Todd Andrew Borlik / William Casey Caldwell / Matt Carter / Kevin Chovanec / John S. Garrison / Scott Oldenburg / Matteo Pangallo / Jamie Paris / Vimala C. Pasupathi / Kyle Pivetti / Margaret Tudeau-Clayton"-- Provided by publisher